Pulmonary Tuberculosis: A Diagnostic and Management Challenge in Pregnancy - Silva, ita; Tavares, Madalena; Melo, Marta; Ribeiro, Andreia; Ambrósio, Paula; Tapadinhas, Paula (Gazeta Médica, 2021)
Tuberculosis is an infectious disease whose prevalence has been decreasing significantly in Portugal. Of the infected patients, only 10% will develop the disease, and this risk is higher in immunocompromised populations. The authors describe a case of a pregnant woman, previously healthy and without epidemiological context, whose diagnosis of tuberculosis was established at 32 weeks of gestation, after having started an unspecific symptom. The diagnostic confirmation and the establishment of anti-bacillary therapy were swift allowing a favorable maternal-fetal outcome. Delivery occurred at 36 weeks without complications. The newborn immediately started chemoprophylaxis, which was maintained until confirmation of absence of disease. The mother continued follow-up in a pulmonology consultation in the Center of Pneumological Diseases, with good clinical, radiological and laboratory evolution, having been discharged without active disease.